2023
DOI: 10.3390/ma16217046
|View full text |Cite
|
Sign up to set email alerts
|

A Review: Design from Beta Titanium Alloys to Medium-Entropy Alloys for Biomedical Applications

Ka-Kin Wong,
Hsueh-Chuan Hsu,
Shih-Ching Wu
et al.

Abstract: β-Ti alloys have long been investigated and applied in the biomedical field due to their exceptional mechanical properties, ductility, and corrosion resistance. Metastable β-Ti alloys have garnered interest in the realm of biomaterials owing to their notably low elastic modulus. Nevertheless, the inherent correlation between a low elastic modulus and relatively reduced strength persists, even in the case of metastable β-Ti alloys. Enhancing the strength of alloys contributes to improving their fatigue resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…The metastable β structure of the Ti 80 -Nb 10 -Mo 5 -Sn 5 (at%) MEA is achieved by adjusting the molybdenum equivalent ([Mo] eq ) to 15 and the valence electron concentration (VEC) to 4.2, which results in the low elastic modulus of the alloy. The thermodynamic parameters detailed in Table 1 were determined using calculations based on the formulas referenced in [9]. These ingots were prepared using a commercial arc-melting vacuum pressure casting system (A-028, DAWNSHINE, Taichung, Taiwan) with pure Ti (99.7 wt%), Nb (99.95 wt%), Mo (99.95 wt%), and Sn (99.9 wt%).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The metastable β structure of the Ti 80 -Nb 10 -Mo 5 -Sn 5 (at%) MEA is achieved by adjusting the molybdenum equivalent ([Mo] eq ) to 15 and the valence electron concentration (VEC) to 4.2, which results in the low elastic modulus of the alloy. The thermodynamic parameters detailed in Table 1 were determined using calculations based on the formulas referenced in [9]. These ingots were prepared using a commercial arc-melting vacuum pressure casting system (A-028, DAWNSHINE, Taichung, Taiwan) with pure Ti (99.7 wt%), Nb (99.95 wt%), Mo (99.95 wt%), and Sn (99.9 wt%).…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, Ti-rich metastable β high-entropy alloys (HEAs) and medium-entropy alloys (MEAs) have garnered significant attention in the field of biomedical materials [1][2][3][4][5][6][7][8][9]. These alloys are known for their high mechanical strength and low elastic moduli.…”
Section: Introductionmentioning
confidence: 99%
“…Titanium and its alloys are used as biomedical implants owing to their high specific strength, low elastic modulus, and excellent corrosion resistance [1,2]. However, they are bioinert and cannot bond with living bone; thus, surface modification is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Metastable β-Ti alloys with low Young's moduli and bcc structures have been extensively studied and developed [1]. There are several guiding principles for the development of Ti alloys with low Young's moduli, one of which is the reduction of the electron-to-atom ratio (e/a) [5]. The lowness of the e/a is an indicator of the instability of the β phase; it has been shown that a reduction in the e/a reduces the Young's modulus of polycrystalline Materials 2024, 17, 2548 2 of 11 materials [6], as estimated by the Hill approximation [7].…”
Section: Introductionmentioning
confidence: 99%